Nickel silicotungstate-decorated Pt photocathode as an efficient catalyst for triiodide reduction in dye-sensitized solar cells. Issue 42 (28th September 2016) - Jiang, Yanxia; Yang, Yulin; Zhu, Junjiang; Qiang, Liangsheng; Ye, Tengling; Li, Liang; Su, Ting; Fan, Ruiqing
Abstract : SiW11 Ni/Pt composite as a CE shows superior catalytic activity for I3 − reduction in the electrolyte and a high power conversion efficiency of 7.03%. Abstract : A new type of polyoxometalate material, K6 SiW11 O39 Ni(H2 O)· x H2 O (denoted as SiW11 Ni), was successfully synthesized and introduced to a dye-sensitized solar cell (DSSC) with modified traditional Pt as a novel composite counter electrode. The new counter electrode showed superior electrochemical catalytic activity for the reduction of I3 − to I − in analysis utilizing a Tafel-polarization curve, cyclic voltammetry (CV), and electrochemical impedance spectroscopy (EIS). The DSSC assembled with the SiW11 Ni/Pt photocathode exhibited an enhanced performance (7.03%) under the standard AM 1.5G illumination compared to the DSSC with a pristine Pt photocathode (6.65%). Furthermore, the DSSC based on the SiW11 Ni/Pt photocathode had an increased light-harvesting efficiency and was very stable. The results demonstrate that SiW11 Ni/Pt is an alternative and highly efficient counter electrode for dye-sensitized solar cells. Moreover, the facile design strategy is promising for fabricating efficient and inexpensive composite counter electrode catalysts for DSSCs.